2016
DOI: 10.1139/cgj-2015-0596
|View full text |Cite
|
Sign up to set email alerts
|

Permeability anisotropy and resistivity anisotropy of mechanically compressed mudrocks

Abstract: Permeability anisotropy (the ratio of the horizontal to vertical permeability) develops in mudrocks at the macroscale due to heterogeneities such as layering and at the element scale (i.e., within a single homogeneous layer or unit) due to decreasing porosity and increasing platy particle alignment. This work describes new experimental methods and results from a laboratory program using cubic specimens to investigate the evolution of mudrock permeability and resistivity at the element scale. A systematic study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 61 publications
3
7
0
Order By: Relevance
“…For C y , ΔC y will synchronously increase with the ΔC p according to equation (13), resulting a high change rate, correspondingly. The data obtained from laboratory experiments (Adams et al, 2016) shows a similar trend of anisotropy exponent changing with porosity as shown in Figure 4c.…”
Section: Anisotropic F-ϕ Relation Of Fractured Digital Rocksupporting
confidence: 66%
See 2 more Smart Citations
“…For C y , ΔC y will synchronously increase with the ΔC p according to equation (13), resulting a high change rate, correspondingly. The data obtained from laboratory experiments (Adams et al, 2016) shows a similar trend of anisotropy exponent changing with porosity as shown in Figure 4c.…”
Section: Anisotropic F-ϕ Relation Of Fractured Digital Rocksupporting
confidence: 66%
“…However, the simulated results shown in Figure d indicate that the m x > m y , which is opposite to the conclusion deduced from conventional observations. The data obtained from laboratory experiments (Adams et al, ) show a similar trend of formation factor changing with porosity, as shown in Figure e. The laboratory data were measured by experiments on a cubic rock sample, which was constructed by resedimenting both Boston Blue Clay and quartz platy particles.…”
Section: Simulation and Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The ECMS adopted the electric conductivity measurement design proposed by Ramsay () and Adams et al. (). The Kelvin sensing method (four‐terminal sensing method) was used to measure the electric impedance of the effluent ( R eff ).…”
Section: Experimental Setup and Methodsmentioning
confidence: 99%
“…Original pore pressure, core, and geomechanics based studies tested much of this material's in situ behavior. After the cores lost their original water contents, they were ground and homogenized to produce a standard material for laboratory testing using resedimentation techniques (14)(15)(16).…”
Section: Samples Sample Preparation and Experimental Designmentioning
confidence: 99%